Finite difference analysis on radiative flow on a perpendicular plate using the influence of thermal conductivity - D. Iranian; K. Sudarmozhi; S. Karthik; J. Manigandan; Ali J. Chamkha (Forces in Mechanics, 2023)
This study aims to investigate the influence of radiation, thermal conductivity and variable viscosity on natural convective flow on a semi-infinite perpendicular plate. Variable viscosity, thermal conductivity and thermal radiation are considered for the given study. The dimensional governing equations are framed with the use of the mentioned parameters and then these equations were converted into dimensionless equations by applying non dimensional quantities. The main aim of this study is to find the Nusselt number and skin friction for both air and water for considered parameters. Using the finite difference method through Fortran software, numerical solutions to the governing heat equations and dimensionless momentum equations were computed. The results for the parameters thermal conductivity, variable viscosity, radiation, and Prandtl number for both air and water are displayed via various graphs. The skin friction coefficients, Nusselt parameter, and local Nusselt numbers were discussed for both the air and water. The key conclusions of this study are that the succeeding velocity declines as the radiation's increases. By increasing the radiation value and the fluctuation time, the temperature distribution increases. Notably, the temperature profile increases significantly when the variable viscosity parameter decreases.